EXPRESSION ANALYSIS OF ECOSENSITIVE GENES HSP70, GPX, SOD AND MT IN CATLA CATLA FROM THE SEWAGE FED AQUACULTURE SYSTEM IN EAST KOLKATA WETLANDS - ANUPAMA, R R; MITRA, TANDRIMA; GANGULY, SATABDI; MAHANTY, ARABINDA; ROUT, SANGRAM KESHARI; DAS, BASANTA KUMAR; MOHANTY, BIMAL PRASANNA (Journal of the Inland Fisheries Society of India, 2021)
Sewage-fed aquaculture is a unique system and has manifold advantages in developing tropical countries. The fish farmers of Kolkata developed a technique of utilization of domestic sewage for fish culture long back. It is necessary to assess, both short and long term impact of sewage effluents on these wetlands. There are several studies on the hydrological properties of these wetlands; but the studies about environmental impact on fish to the longtime exposure of sewage are scanty. In the present study, expression analysis of ecosensitive genes (hsp70, SOD, GPx and MT) was carried out in liver tissues of Catla catla to evaluate the environmental impact on fish physiology. Fish samples were collected from sewage fed system of Nalban bheri and a rain fed culture pond. Expression of selected genes were observed through semi-quantitative RT-PCR. The expression of all the studied genes showed similar pattern in fishes collected from both the systems. The observations of the present study revealed that, normal physiology of the fish was not affected in the sewage fed aquaculture system. Key words: East Kolkata wetlands, antioxidative gene expression, hsp70, sewage fed systems